Implementation Of Context, Input, Process & Product (CIPP) Model Evaluation In Virtual-Based Practical Learning In The Electrical Power System Laboratory - Dwi Anggaini; Titi Ratnasari; Intan Ratna Sari Yanti (CV ODIS, 2022)
This goal is a shape of laboratory-primarily based totally realistic getting to know for guides completed within the Power System Analysis laboratory. This form of study applies assessment studies with a descriptive quantitative approach. This looks at eleven instructors and 15 college students who were used as samples. The sample indicates that the cost acquired with the aid of utilizing the practicum lecturer in phrases of contextual is 84.090%, in phrases of entering is 90.150%, in phrases of technique is 89.770% and in phrases of product is 87.12%. From the scholar aspect, the effects finished primarily based totally on the expertise of really getting to know withinside the laboratory in phrases of contextual are 80.00%, in phrases of entering 83.660%, in phrases of technique 85.830% 79.160% in phrases of product. Based on the effects of calculations from the lecturer and college students, the digital laboratory-primarily based on totally realistic getting to know goes properly so that college students` expertise is withinside the proper category